2013
DOI: 10.7314/apjcp.2013.14.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Improving Safety-Related Knowledge, Attitude and Practices of Nurses Handling Cytotoxic Anticancer Drug: Pharmacists' Experience in a General Hospital, Malaysia

Abstract: Background: An increasing trend of cytotoxic drug use, mainly in cancer treatment, has increased the occupational exposure among the nurses. This study aimed to assess the change of nurses' safety-related knowledge as well as attitude levels and subsequently to assess the change of cytotoxic drug handling practices in wards after a series of pharmacist-based interventions. Materials and Methods: This prospective interventional study with a before and after design requested a single group of 96 nurses in 15 war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
50
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 14 publications
12
50
2
2
Order By: Relevance
“…Hong (2006) demonstrated that there is a positive relationship between before education (r=0.070, p<0.001) and after education (r=0.570, p<0.001) for the relationship of awareness and practice regarding anticancer drug safety regulations. Also a study by Keat et al (2013) and Kyprianou et al (2010) showed a positive relationship between safety-related knowledge and the practices for handling cytotoxic anticancer drugs .These results are congruent with the results of this study in which a higher level of awareness led to a higher level of performing the safety regulations. This result indicates that safety education is crucial to increasing the actual practice at work.…”
Section: Discussionsupporting
confidence: 87%
“…Hong (2006) demonstrated that there is a positive relationship between before education (r=0.070, p<0.001) and after education (r=0.570, p<0.001) for the relationship of awareness and practice regarding anticancer drug safety regulations. Also a study by Keat et al (2013) and Kyprianou et al (2010) showed a positive relationship between safety-related knowledge and the practices for handling cytotoxic anticancer drugs .These results are congruent with the results of this study in which a higher level of awareness led to a higher level of performing the safety regulations. This result indicates that safety education is crucial to increasing the actual practice at work.…”
Section: Discussionsupporting
confidence: 87%
“…Keat et al carried out an interventional study where they investigated effects of courses and workshops on knowledge about safe practices while working with cytotoxic drugs in nurses. They showed significant benefits of these interventions on nurses knowledge (Keat et al, 2013). Khokhar et al handled training workshops about breast cancer and screening guidelines for 259 nurses.…”
Section: Discussionmentioning
confidence: 99%
“…On the same line, Keat, Sooaid, Yun, and Sriraman, (2013) [3] reported that there was a significant improvement of knowledge levels among the nurses on cytotoxic drug handling, with comparison of a mean knowledge score in the first and the second assessment after implementation of a series of technical, educational and administrative support measures consisting of the initiation of closed-system cytotoxic drug reconstitution (CDR) services, courses, training workshops and guideline updates in their study that titled "improving safetyrelated knowledge, attitude and practices of nurses handling cytotoxic anticancer Drug: pharmacists' experience in a general hospital, Malaysia".…”
Section: P-value T-testmentioning
confidence: 99%
“…But post implementation of educational sessions, there was improving in the knowledge and skills of nurses in their study that titled "assessment of knowledge, skill and attitude of oncology nurses in chemotherapy administration in tertiary hospital Pakistan". Also, Keat, et al, (2013) [3] reported that the mean score for overall ward practices was increased twofold, from 7.6-15.3 out of 20.0. All tested aspects including the drug preparation, transportation, storage, administration, spillage management and waste disposal and decontamination were significantly improved after the interventions in their study that titled "improving safety-related knowledge, attitude and practices of nurses handling cytotoxic anticancer Drug: pharmacists' experience in a general hospital, Malaysia".…”
Section: P-value T-testmentioning
confidence: 99%
See 1 more Smart Citation